MARRIAGE CONTRACT THROUGH VISUALIZATION OF ONLINE VIDEO CALL COMMUNICATION MEDIA ACCORDING TO MARRIAGE LAW AND ISLAMIC LAW IN INDONESIA - Faisal, F.; Isnaeni, Ahmad; Bahrudin, Moh.; Nasruddin, N. (Universitas Islam Negeri Raden Intan Lampung, 2021)
Talks about marriage always attract attention, not because it contains discussions about sexuality, but because marriage is a sacred event in religious teachings. Not only as a civil bond between individuals in general, but a bond that has to worship values, and is the longest worship practice in Islamic history. Marriage is valid if the pillars and conditions are met, one of which is ijab and qabul. The problem point arises when the ijab and qabul pledged by the parties are not in the same assembly, but in different places remotely through online communication media video call. To solve this problem, this study uses approach normative theological and normative juridical. Data analysis was carried out qualitatively, and conclusions were drawn using deductive thinking. The results of this study are that the marriage contract through online communication media video call has basically fulfilled the pillars and requirements for a valid marriage and does not conflict with the compilation of Islamic law. However, scholars differ on the validity of the marriage contract through online communication media video calls. This difference of opinion is caused by different understandings of the meaning of “Ittihad al-majlis”. One group of scholars defines it in a physical sense and another group in a non-physical sense.Keywords: Marriage Contract, Online Video Call Communication Media, Marriage Law, Islamic Law.